REMEDIASI KESALAHAN MENYELESAIKAN SOAL USAHA ENERGI MENGGUNAKAN STRATEGI SYSTEMATIC APPROACH TO PROBLEM SOLVING DI SMA - Wulandari Wulandari; Stepanus Sahala Sitompul; Syukran Mursyid (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2020)
The aim of this research is to find out the effectiveness of using Systematic Approach Strategy on remedy to reduce the total incorrect results on answering the test on the topic of work and energy on the students at SMA Negeri 1 Batu Ampar. The population in this research are 72 students. Technique of data collection in this research is intact group with 36 students as the sample. The research implements experiment method. The research use limited topic on the test consist of work and energy. Statistic test used in this research is Wilcoxon  with value  = -0.1631, if this results are compared with value  on taraf nyata  = 0.025, it resulted, with the value 0.1631 < 1,96. After analyze found that there are no significant differences on the total incorrect results on answering the test on the topic of work and energy by students at XI MIPA SMA Negeri 1 Batu Ampar before and after remedy. The Conclusion from the results found that the strategy can reduce the total incorrect results of the students answering the test on the topic of work and energy with effectiveness low at the average 11.18%.Keywords: